Reappraisal of a 2-cm Cutoff Size for the Management of Nonfunctional Pancreatic Neuroendocrine Tumors: A Population-Based Study - Yang, Zhen; Zhang, Dongsheng; Shi, Guangjun (Frontiers in Endocrinology, 2022)
Abstract Background: Expectant observation or aggressive surgery are both recommended for small non-functional pancreatic neuroendocrine tumors (NF-PanNETs). However, the optimal management of small NF-PanNETs remains disputable due to the heterogeneous clinical behavior. Methods: Patients who were diagnosed with pancreatic neuroendocrine neoplasms (PanNENs) between 2000 and 2018 were identified from the surveillance, epidemiology and end results (SEER) database and reviewed retrospectively. Tumor aggressiveness was defined as poor differentiation, lymph node involvement, liver involvement, and advanced stage. The best cut-off of tumor size associated with tumor aggressiveness was determined through the Receiver operating characteristic (ROC) curve analysis. Univariate and multivariate analyses were used to identify prognostic factors in patients with tumors ≤2cm. Results: A total of 5172 patients with PanNENs were enrolled, including 1760 (34.0%) tumors≤2cm and 3412 (66.0%) tumors>2cm. A 2.5cm cutoff size was found to be associated with a satisfactory ability in predicting tumor aggressiveness. On multivariate analysis, age, gender, ethnicity, tumor grade, tumor number, and stage were independent prognostic factors for overall survival (OS) in patients with tumors less than 2cm in size. 1621 patients were diagnosed with NF-PanNETs according to the WHO classification, of whom 1350 underwent surgery, 271 performed active observation. The OS was significantly better in the surgery group compared to observation group regardless of propensity score analysis. Additionally, a total of 407 patients were selected based on the multivariate Cox regression analysis, of whom 46 underwent observation, 361 underwent surgery, and the OS was comparable. Conclusion: Expectant observation of small NF-PanNETs may be a reasonable alternative to aggressive surgical resection in highly selected small NF-PanNETs patients. And the decision to observation versus surgery should not only be based on tumor size alone, but also take into account other important clinicopathological factors.